Writing Strategies across four disciplines in a Tunisian Context - Dallagi, Maha (International Journal of Language and Literary Studies, 2020)
English is now widely established as the world language for information exchange, communication, and conducting research (Cenoz & Jessner, 2000; Wood, 2001); and developing satisfactory writing strategies is crucial. Writing is a challenging skill, the complexity of which is mainly felt at University Level. This paper investigated writing strategies among 147 Tunisian university students, majoring in Hard Science and Soft Science courses (English, French, Medicine and Engineering). Its objective was to verify to what extent factors such as academic field, gender, and proficiency interact with each other and with writing strategies. A Survey of Writing strategies was adopted as the main investigating instrument. Findings reveal that Language majors are higher users of strategies than other majors, yet this does not seem to impact their proficiency level. The results suggest raising students’ awareness of Writing strategies by teaching them explicitly and drawing their attention to them.